Passive Cooling Implementation in Urban House (Study Case : Rumah Perahu Merah-Putih, Malang) - Azka Stanza Budhiputranto; Agung Murti Nugroho (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
Global warming is one of the main issues that require solutions for the survival of the earth and humans in the present and the future. Buildings, especially dwellings in modern urban conditions, are one of the sectors that have also received the impact of global warming, as well as raising issues in the exploitation of energy and natural resources. Understanding of nature by using an ecological approach is expected to be able to maintain the balance of nature. Human thermal comfort is needed for humans to be able to support activities in space. Factors that influence the thermal comfort of space are less noticed and tend to be solved by artificial ventilation. “Rumah Perahu Merah-Putih as one of the good precedents in applying the concept of tropical architecture in residential buildings was chosen because it applied one of its principles by using tropical walls, namely the design of walls with apertures and ventilation ducts. In order to optimize passive cooling performance so that space can achieve thermal comfort without using artificial energy.